PENCATATAN AKTA NOTARIS AKAD SYARIAH OLEH NOTARIS NON MUSLIM PERSPEKTIF HUKUM ISLAM - Zaid Raya Argantara; Zainurrohman Zainurrohman (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2021)
Law Number 21 of 2008 concerning Sharia Banking, shows that the sharia economic system, especially in the banking sector, has legal legitimacy and legal certainty in a formal juridical manner. or the agreement. However, with the many existing Islamic financial institutions, it is possible to use the services of a non-Muslim notary in making the sharia contract deed. The competence and authority of the notary in charge of recording the sharia contract is needed to be accepted in the eyes of law and sharia.This research is a type of library research, where in this study the main data source is to explore concepts/theories that have been determined by previous experts which are stored in the form of books, journals, newspapers, magazines, articles, and so on.The results of the study show that: first, a Notary is an official appointed by law to make a deed, even a sharia deed as long as it is not excluded from the authority of his position as regulated in Article 15 paragraph 1 UUJN which confirms that one of the powers of a notary is to make deed in general. Second, the law of being a notary is fardhu kifayah so that if someone has implemented it, then others are free from this responsibility. And in Islam there is no problem with who we do muamalah with, even if it is a non-Muslim.